Archetypes and Motifs in Folklore and Literature: A Handbook: A Handbook, 1st edition - Garry, Jane (Routledge, 2020)
This is an authoritative presentation and discussion of the most basic thematic elements universally found in folklore and literature. The reference provides a detailed analysis of the most common archetypes or motifs found in the folklore of selected communities around the world. Each entry is written by a noted authority in the field, and includes accompanying reference citations. Entries are keyed to the Motif-Index of Folk Literature by Stith Thompson and grouped according to that Index's scheme. The reference also includes an introductory essay on the concepts of archetypes and motifs and the scholarship associated with them. This is the only book in English on motifs and themes that is completely folklore oriented, deals with motif numbers, and is tied to the Thompson Motif-Index. It includes in-depth examination of such motifs as: Bewitching; Chance and Fate; Choice of Roads; Death or Departure of the Gods; the Double; Ghosts and Other Revenants; the Hero Cycle; Journey to the Otherworld; Magic Invulnerability; Soothsayer; Transformation; Tricksters.